Environmental benefits of planting fast-growing trees on eroding cropland in Java - Van Dijk, Albert I.; Bruijnzeel, L.A.; Vernimmen, Ronald R.E. (BOIS & FORETS DES TROPIQUES, 2004)
Le résumé en français est disponible dans le fichier PDF de l'article. Fast-growing albizia (Paraserianthes falcataria) trees are being planted to an Increasing extent in the degraded uplands of Java. We studied biomass and carbon dynamics in these forests and on the bench-terraced cropland they replace. Carbon is lost from cropland through harvesting and eroded sediment, but the plantations appear to recycle carbon back into the soil at very high rates. Combined with beneficial effects on erosion and soil nitrogen content, albizia plantation forestry may offer considerable potential for soil improvement and carbon sequestration. (Résumé d'auteur)